2000
DOI: 10.1007/s004050050215
|View full text |Cite
|
Sign up to set email alerts
|

Sialolithiasis in children as a diagnostic dilemma

Abstract: Sialolithiasis is an uncommon disorder in childhood. Initially asymptomatic, symptoms may appear gradually. These can vary from moderate discomfort to severe pain with large glandular swelling accompanied by trismus. The correct interpretation of symptoms and a proper investigation for localization of salivary stones are important for effective treatment. A case of submandibular sialolithiasis in a 9-year-old girl is used to exemplify the problems had in clinical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…Pediatric sialolithiasis is a rare disease entity, with less than 120 cases having been reported in literatures [1][2][3][4][5][6][7][8][9][10][11]. In this study, we reviewed the largest reported number of pediatric cases in a single study so as to clarify the distinguishing clinical features relative to adult cases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Pediatric sialolithiasis is a rare disease entity, with less than 120 cases having been reported in literatures [1][2][3][4][5][6][7][8][9][10][11]. In this study, we reviewed the largest reported number of pediatric cases in a single study so as to clarify the distinguishing clinical features relative to adult cases.…”
Section: Discussionmentioning
confidence: 93%
“…intermittent reports of case series in the literature, and the absence of comprehensive analyses thereof [2][3][4][5][6][7][8][9][10][11]. When physicians meet the children with salivary gland swelling and pain, sialolithiasis must be included in the differential diagnosis, because of rapid improvement after adequate management for sialolithiasis, compared to other chronic inflammatory diseases.…”
mentioning
confidence: 99%
“…Extraoral transcutaneous ultrasonography can also show the location of stones, and, advantageously, detect radiolucent stones and be used in patients with acute sialadenitis [10]. When other investigations have failed to detect calculi in patients suspected with salivary gland stones, CT can help confirm a diagnosis and localize the stone [9]. At present, MR is not helpful in the detection of stones [3].…”
Section: Discussionmentioning
confidence: 95%
“…Sialography has up to 100% diagnostic accuracy. However, its use is contraindicated in (i) acute infections because of risk of extravasation and (ii) orifice stones for fear of posterior displacement of calculi [9]. Extraoral transcutaneous ultrasonography can also show the location of stones, and, advantageously, detect radiolucent stones and be used in patients with acute sialadenitis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Sialolithiasis accounts for 80% of sialadenitis within Wharton's duct [3]. Salivary calculi are uncommon in children, comprising only 3% of cases [4,5]. Although sialolithiasis is unusual in children, it is useful to have alternative techniques to conventional surgery.…”
mentioning
confidence: 99%